The Impact of Academic Digital Literacy on Career Adaptation Among Recent Undergraduate Graduates - Zainul Anwar; Djudiyah Djudiyah; Nida Hasanati; Ahmad Sulaiman (STAI Hubbulwathan Duri, 2025)
Graduate unemployment remains a pressing issue in Indonesia, with a 5.98% open unemployment rate among university graduates reported by the Central Bureau of Statistics (BPS) in 2021. Contributing factors include a misalignment between academic preparation and labor market needs, limited work experience, and inadequate readiness for professional roles. Strengthening career adaptability during the transition from university to the workforce is essential. This study employed a quantitative experimental design to examine the impact of academic digital literacy training on career adaptability among recent undergraduate graduates. Participants completed pre- and post-tests measuring career adaptability before and after the intervention. The analysis revealed a statistically significant increase in participants' career adaptability scores following the training. The intervention notably improved graduates’ readiness to meet workforce demands by enhancing their digital competencies relevant to both academic and professional contexts. These findings indicate that academic digital literacy training plays a critical role in bridging the gap between university education and workplace expectations. By equipping graduates with essential digital skills, the program supports a smoother transition into professional roles and may contribute to reducing graduate unemployment. Integrating academic digital literacy into higher education curricula can effectively enhance career adaptability and employment readiness. Institutions should prioritize such training to better align graduate skills with evolving labor market demands.